Natural business English : authentic language for business today - Mascull, Bill, ....- (Peaslake : Delta Publishing, 2013)
Suitable for people who want to learn the real language of international business, this title covers essential business vocabulary and expressions as well as presenting and practising authentic business language, using idiomatic expressions and metaphorical language.
Keywords: Zakelijke communicatie : Engels; Engels zakenleven; Engels taalgebruik